Plunging into the process: methodological reflections on a process-oriented study of stakeholders' relating dynamics. Issue 1 (2nd January 2020) - Vandenbussche, Lieselot; Edelenbos, Jurian; Eshuis, Jasper
ABSTRACT: Process-oriented approaches increasingly gain attention within policy and administrative studies. A process orientation emphasizes the ongoing, dynamic character of policy phenomena, i.e. their becoming. This article reflects upon the methodological particularities and challenges that come with doing process-oriented research. To do so, it draws on experiences with a concrete process study on stakeholders' relating dynamics within a collaborative policymaking process. This article identifies three methodological particularities: (1) the ongoing amplification of realities, (2) the shifting of positionalities of both researchers and participants, through time and across contexts, and (3) the emergence of historical-aware reflexivity. While each of these are common issues in qualitative-interpretive research, we argue how the longitudinal and poly-contextual orientation of a process study amplifies their impact on the research process and poses specific challenges. We conclude that to effectively deal with these particularities and challenges a process researcher benefits from developing and establishing good field relations, as well as from the courage to come to 'temporary' closure(s), against the background of the continuously becoming of the phenomenon under study.